Effect of Different Weed Management Practices on Weeds and Yield of Cumin - Mehriya, M L; Yadav, R S; Jangir, R P; Poonia, B L (Annals of Arid Zone, 2016)
Chenopodium mumle, C. album and Rumex dentatus were the predominat weeds in the experimental field. Oxyfluorfen at 50 or 75 g ha'l, and oxadiargyl at 50 g ha'l applied at 20 DAS along with one hand weeding at 35 DAS, being at par among themselves, brought maximum reduction in weed biomass production of Chenopodium spp. as wel1 as total weeds, thereby recording (93.9-96.2%) higher weed control efficiency. However, maximum dry .weight of Rumex dentatus was reduced due to the application of paraquat at 0.4 kg ha'l + one hand weeding. Integration of oxyfluorfen at 50 or 75 g ha'l along with one hand weeding gave . comparable seed yield to weed free check and consequently provided maximum B:C ratio (2.92). Oxadiargyl+hand weeding resulted in statistical1y at par seed yield to that obtained with combined application of oxyfluorfen+hand weeding. Amongst the sole herbicidal treatments, oxyfluorfen 50 or 75 g ha,l or oxadiargyl 50 g ha'l applied at 20 DAS recorded higher WCE (83.3-88.9%) and produced significantly higher growth and yield attributing characters which led to higher seed yield, net returns and B:C ratio compared to fluchloralin 1.0 kg ha-1 PPI (recommended herbicidal control)] Key words: Cumin, weeds, herbicide, weed control efficiency